O Processo de desenho urbano em conjuntos habitacionais - Rigatti, Décio (Paisagem e Ambiente, 1998)
This paper aims to deal with som e basic concepts concerning urban analysis such as urban space; configuration; order; structure; form ; function; am ong others. These concepts allow a more rigorous evaluation of urban desiqn in general and specially the design of housing estates. Particularly regarding som e recent experiences in designing housing estates in Brazil, it is sought to provide an analytical tool in order to understand the deep differences found when urban morphologies layed out by designers are compared to those actually built up by thed wellers of those settlements as they occupy space